Healthcare Malaysia at a crossroads - Abd. Manaf, Noor Hazilah (IIUM Press, International Islamic University Malaysia, 2018)
Healthcare Malaysia at a Crossroads discusses aspects of the country’s healthcare delivery system that are impacted by changes that have altered our healthcare landscape, from medical education to medical tourism. Globalisation, changing demography, privatisation, and liberalisation of medical education are just some of the change variables affecting our healthcare system today. The book begins with an exploration of medical education and housemanship training; and dimensions of preparedness for hospital practise among the junior doctors during the housemanship period. This was followed through by an assessment of the evolutionary path towards medical specialisation, and consequently issues concerning medical specialty training in the country. A significant development which has taken the healthcare industry by surprise, in the form of medical tourism, is given further treatment in subsequent chapters. The background to medical tourism in Malaysia, an interdisciplinary perspective of the industry, as well as evaluation of service quality and future intention of medical tourists to seek treatment in the country is also examined. A report card on our performance vis-a-vis our neighbouring countries provides a critical analysis. The main aim of the book is to explore issues in Malaysian healthcare system that requires our attention. Medical education and training; and opening our hospital doors to foreign patients do impact the services that we receive from our healthcare system. We have developed a healthcare system that is both equitable and accessible; and the purpose of the book is to contribute to the discourse on how to make it better.